Statistical Analysis on Influence of Biology Laboratory Practical on Senior Secondary Students’ Academic Performance in Ilorin East Lga, Kwara State - Florence Omosholape Abidoye; Abidoye A. Omotayo (PT FORMOSA CENDEKIA GLOBAL, 2023)
High achievement especially in Biology is usually enhanced by proper Biology laboratory practical. However, it is assumed that most Biology teachers resort strictly to the use of theoretical method in teaching. This has constantly led to poor performance of students in the Senior Secondary School Certificate Examination across Nigeria. Therefore, this study investigated the statistical analysis on influence of Biology laboratory practical on students’ academic performance of Senior Secondary Students in Ilorin East, Kwara State, Nigeria. The study was a descriptive survey type. One hundred and twenty (120) students were sampled for the study using proportionate and simple random sampling technique in Ilorin East L.G.A, Kwara State, Nigeria. A researched designed questionnaire was used to accumulate information from respondents. Three research questions and two research hypotheses formulated were tested using percentage, mean, frequency count and independent t. test and ANOVA at 0.05alpha level of significant. The result of findings revealed that Biology laboratory practical has a great influence on senior secondary school students' academic performance and also on the level of understanding and retention capabilities of students but there was no significant influence of Biology laboratory practical on students’ academic performance based on gender but not was significant based on class size. It is thus recommended that; all Biology teachers should engage students more in pratical activities more than the theory aspect to facilitate better understanding among the students, Ministry of Education should provide adequate laboratory equipment and good laboratory environment to promote spirit of curiosity in students and stakeholders should build more infrastructure such as laboratories, classrooms and others.